Perhitungan Debt to Equity Ratio (DER), Return on Equity (ROE), Earning Per Share (EPS) Pada Bank Rakyat Indonesia Tbk Periode 2021-2022 - Fauziyah, Hikmah; Putra, Jamal Handitia; A, Alfanny; Nurfadilah, Diktia; Suherman, Ujang (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to determine the calculation of the Debt to Equity Ratio (DER), Return On Equity (ROE), and Earning Per Share (EPS) at PT Bank Rakyat Indonesia Tbk for the 2021–2022 period. The method used is descriptive, which uses quantitative data, namely the PT Bank Rakyat Indonesia Tbk financial report as the population. The data used in the study comes from the financial statement of the issuer, PT Bank Rakyat Indonesia Tbk, for the period 2021–2022. From the financial statement data of PT Bank Rakyat Indonesia Tbk for 2021–2022, calculations can be obtained that include the Debt to Equity Ratio (DER), Return On Equity (ROE), and Earning Per Share (EPS).